Mothers and fathers facing their children's phenylketonuria. Issue 1 (2nd January 2018) - Ionio, Chiara; Salvatici, Elisabetta; Confalonieri, Emanuela; Milani, Luca; Mascheroni, Eleonora; Riva, Enrica; Giovannini, Marcello
ABSTRACT: The aim of this study is to understand the impact of children's phenylketonuria (PKU) on mothers and fathers and to assess the mutual influence of the psychological functioning of one parent on the other. 33 mothers and 33 fathers of PKU-affected children and 43 mothers and 43 fathers of non-PKU-affected children were involved. All of the parents filled out the Los Angeles Symptoms Checklist, the Profile of Mood Scale, the Parenting Stress Index-Short Form, and the Coping Health Inventory for Parents. We performed parametric intergroup analysis and multiple regressions. Results pointed out that there is a link between maternal stress and maternal negative states of mind, trauma-related symptoms, and paternal coping strategies. As regards fathers, there is a link between paternal stress and maternal trauma-related symptoms. Our findings suggest it will be important to better investigate the role played by paternal response in supporting mothers of a chronically ill child, since they confirm the importance of taking into account the points of view of both mothers and fathers and their mutual influences in responding to PKU diagnosis.